ARABIC CONSTRUCTION AND OWNERSHIP INSCRIPTIONS FROM THE SECOND HALF OF THE 19TH CENTURY IN YALAK VILLAGE, AKHTYNSKY DISTRICT OF DAGESTAN - Zakariaev, Zamir Sahbanovic (History, Archeology and Ethnography of the Caucasus, 2024)
This article aims to present the results of a study on select Arabic epigraphic monuments discovered by the author in the mountainous Lezgin village of Yalak, located in the Akhtynsky district of Dagestan. It introduces the content of eight Arabic inscriptions from the second half of the 19th century, categorized within the genres of construction texts and related ownership inscriptions. Some of the published inscriptions are hybrid in nature. For instance, the inscription above the entrance to the Juma Mosque represents a synthesis of two genres of Arabic epigraphy in Dagestan – construction inscriptions and the historical-legal genre of “agreements” (ittifaq). All presented inscriptions are dated and were composed to commemorate the completion of renovation and construction work on the Juma Mosque and private residential buildings. The inscription plates are adorned with decorative elements, with some exemplifying high-quality specimens of Dagestani stone carving art. These inscriptions contain the names of private homeowners, professional builders, calligrapher-carvers, and elected village elders, all of whom were residents of Yalak. The social terminology used in the texts is of particular interest. The construction and ownership inscriptions from Yalak, as well as from other villages in the Akhtynsky district, are often accompanied by moral admonitions, philosophical maxims, and excerpts from medieval poetic works. It has been determined that the verses of ‘Ali ibn Abi Talib (d. 661) were most favored by the inscription composers in the region. Translations and descriptions of the Arabic texts are provided with commentary. The prosopographical information from the inscriptions is supplemented with archival data, including the Population Census of Yalak village from 1850, 1865, 1873, and 1886.
Keywords: Arabic epigraphy; Dagestan; Yalak; Lezgins; construction inscriptions; ownership inscriptions